Removal of Cu (II) and Mg (II) by using modified mesoporous silicates MCM-41 and SBA-15 from aqueous solution / Faustina Elfrida Anak Sangok - Anak Sangok, Faustina Elfrida (2014)
The objective of this research was to develop an effective and efficient heavy metal ions adsorbent with high removal percentage at various optimum conditions. In this research, mesoporous silicate, Santa Barbara Amorphous- 15 (SBA-15) and Mobil Composition Matter-41 (MCM-41) were modified by using 3-aminopropyltriethoxysilane (APTES), 3-mercaptopropyltrietoxysilane (MPTS) and triethoxyvinylsilane (TEVS) to produce adsorbents. Six types of modified mesoporous silicate namely; ASBA-15, MSBA-15, TSBA-15, AMCM-41, MMCM-41 and TMCM-41 were synthesized and tested as heavy metal ions adsorbent. These adsorbent were characterized for their mesoscopic array, crystalinity, functional group, surface morphology, percentage and decomposition of organic component. Adsorption study was carried out at various parameters, namely contact time, concentration, pH, temperature, agitation speed and adsorbent dosage. Optimum condition for removal of Cu (II) ions was found to be at 30 minutes, 150 mg L'1, pH 5, 25°C, 400 rpm and 0.05 g adsorbent whereas for Mg2+ ions, the highest removal percentage was at 240 minutes, 150 mg L'1, pH 3, 25°C, 800 rpm and 0.05 g adsorbent. ASBA- 15 was found to show the highest efficiency to adsorb Cu (II) whereas AMCM-41 was found to show the highest efficiency to adsorb Mg (II). Equilibrium adsorption study was carried out to study isothermal model. Langmuir isotherm was well fitted to adsorption study compared with Freundlich isotherm, with favorable adsorption process. Meanwhile, kinetic study was carried out and adsorption process was found to be best presented by using pseudo-second order kinetic model with correlation coefficient R2>0.99. Adsorption process also was found to be controlled by intraparticle diffusion and was found to occur spontaneously. Regeneration of adsorbent was done by two methods, EDTA treatment and acid-base treatment. It was found that EDTA treatment was a better choice of regeneration with 90% of heavy metal recovery. This indicated that an efficient adsorbent have been successfully synthesized.